A DESIGN OF SPEAKING ASSESSMENT RUBRIC FOR ENGLISH IMMERSION CAMP - Ummu Syahidah; Faujia Umasugi (Universitas Muhammadiyah Makassar, 2021)
The aim of this mix-method study is to design a speaking assessment rubric for an English Immersion Camp (EIC) program in Muhammadiyah University of North Maluku called UMMU English Immersion Camp (UEIC). In UEIC, there were seven activities applied for triggering the participants to continuously speak English during the program (see Syahidah, Umasugi, Buamona, 2019). However, the program did not have a proper assessment form to measure the UEIC participants’ speaking development. Therefore, this study was administered to design the assessment in the form of a speaking rubric. Three instruments were used to gather the data for designing the rubric. Interviews were adminstered to two experts of English language assessment who have been having years of experince in teaching English at the university. Document analyses were done to analyze the UEIC syllabus from previous studies and speaking rubrics from various sources to make a match between the design of the assessment instrument with the UEIC achievement targets, objectives, materials, and learning techniques. Observations were conducted by four observers who were fasilitators at the UEIC to measure the participants’ speaking progress. Data from obervations were used to test the validity and reliability of the rubric. The speaking assessment rubric was designed based on the steps of designing speaking assessment proposed by O’Malley and Pierce (1996) which are identifying the purposes of speaking assessment, planning speaking assessment, developing speaking test rubric and setting standards. The rubric contained ten items divided into six aspects of speaking assessments namely (1) grammar, (2) vocabulary, (3) pronunciation, (4) fluency, and (5) comprehenesibility respectively represented into two items, and (6) accuracy measured by three items. Moreover, the validity and reliability analyses showed that the rubric containing 10 items were valid and reliable because all values needed have reached the theoretical standard value for validity and reliability of a speaking test instrument.